2023
DOI: 10.3389/fpls.2023.1128928
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of key physio-biochemical traits and molecular network conferring heat stress tolerance in cucumber

Abstract: Cucumber is an important vegetable crop grown worldwide and highly sensitive to prevailing temperature condition. The physiological, biochemical and molecular basis of high temperature stress tolerance is poorly understood in this model vegetable crop. In the present study, a set of genotypes with contrasting response under two different temperature stress (35/30°C and 40/35°C) were evaluated for important physiological and biochemical traits. Besides, expression of the important heat shock proteins (HSPs), aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 96 publications
2
2
0
Order By: Relevance
“…By means of the stepwise regression equation, H 2 O 2 and Fq′/Fm′ were retained as significant predictors, indicating their substantial contribution to heat resistance in cucumber (Figure 6). H 2 O 2 and Fq′/Fm′ were involved in photosynthetic and oxidation system, which is consistent with most articles on heat resistance research (Zhou et al, 2017; Yu et al, 2018; Hongal et al, 2023). The findings demonstrated that the method is reliability.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…By means of the stepwise regression equation, H 2 O 2 and Fq′/Fm′ were retained as significant predictors, indicating their substantial contribution to heat resistance in cucumber (Figure 6). H 2 O 2 and Fq′/Fm′ were involved in photosynthetic and oxidation system, which is consistent with most articles on heat resistance research (Zhou et al, 2017; Yu et al, 2018; Hongal et al, 2023). The findings demonstrated that the method is reliability.…”
Section: Discussionsupporting
confidence: 89%
“…indicating their substantial contribution to heat resistance in cucumber (Figure 6). H 2 O 2 and Fq 0 /Fm 0 were involved in photosynthetic and oxidation system, which is consistent with most articles on heat resistance research (Zhou et al, 2017;Yu et al, 2018;Hongal et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, we have investigated the role of the photosynthetic activities at the seedling and reproductive stages of the cucumber plants in maintaining the green colour of the fruits for an extended period. The higher photosynthetic rate in the genotypes with the ability to retain the green colour of the leaves is reported in cucumber genotypes with heat stress tolerance (Hongal et al 2023). It was observed that the genotype with extended shelf-life, DC-48, was able to maintain a steady rate of photosynthesis both at the seedling and reproductive stages.…”
Section: Discussionmentioning
confidence: 84%